Plantas medicinais usadas em comunidades rurais no distrito de União do Norte (Peixoto de Azevedo, Mato Grosso) : conhecimento como subsídio à conservação - Carbolim, Roseli Lourdes (2023)
Ethnobotany is an area of science that seeks to relate the plant world and human knowledge, involving popular knowledge. Medicinal plants are important for traditional communities as they are widely used in the relief or treatment of low-complexity diseases. In addition to being the basis for further studies in the prospect of new drugs that can be synthesized by the industry. In this way, the present study aimed to identify the use of medicinal plants and how this knowledge is passed on to future generations in rural communities in the district of União do Norte in Peixoto de Azevedo, northern region of Mato Grosso, aiming to contribute to the conservation of traditions and, consequently, of the plant species used by the local population. Altogether 58 species from 34 botanical families were cited in the study. The most cited plants were mint (Mentha piperita L.), boldo (Plectranthus barbatus Andr.), and lemongrass (Cymbopogon citratus (DC. ) Stapf)). Regarding the parts most used in the preparations, the leaf was the most cited part for the preparation of tea to relieve or cure various symptoms. The Informants' Consensus Factor categories ranged from 0.66 to 0.81, showing agreement between informants even though they did not present a maximum value of 1. In general, it was evidenced that the use of medicinal plants, their preparation for treatment of low-complexity diseases is a reality in the communities studied, as well as the importance of women in this process, since they corresponded to the majority of respondents (75.0%), acting strongly so that this culture remains alive in the communities and the knowledge passed on for future generations.